Profiling of microRNA from skeletal muscle of Bandur sheep using RNA sequencing - MANDEEP, KAUR; ASHISH, KUMAR; S, NAVEEN KUMAR; NADEEM, FAIROZE MOHAMED; SONIKA, AHLAWAT; KUMAR, VIJH RAMESH; ANITA, YADAV; REENA, ARORA (The Indian Journal of Animal Sciences, 2021)
MicroRNA profiling is a powerful approach for identifying key regulators of molecular functions which control skeletal muscle development, regeneration and function. Information on gene expression and the regulatory factors involved in myogenesis is very limited for Indian sheep. This study reports the identification and characterization of miRNAs from the skeletal muscles of Bandur sheep breed for the first time. Bandur is a consumer favoured, mutton type sheep of India, mainly distributed in Mandya district of Karnataka. Skeletal muscles from four animals of Bandur sheep of similar age, sex and reared under same management conditions were used for RNA sequencing. The total number of reads (15–36 bp) for each library of Bandur sheep ranged from 19,350,000 to 30,000,000. Highly expressed transcripts with an RPKM value of ≥1000 were observed to be 34%, whereas 38% transcripts exhibited RPKM between 100–1000 and 28% had RPKM